Translation Strategies and Nomenclature in The Spiderwick Chronicles and its Finnish Translation - Raikunen, Ida (My University, 2026)
This thesis explores the translation strategies used to translate nomenclature in The Spiderwick Chronicles (2009) by Holly Black and Tony DiTerlizzi. The material was collected from said novel and its Finnish translation, Spiderwickin kronikat (2008) by Ulla Lempinen. The aim of this thesis is to analyse what translation strategies the translator has used and discuss why certain strategies have been used for certain names. The theoretical part of this thesis is largely produced by Van Coillie, who has introduced ten possible strategies for translating proper nouns. Additionally, other authors and their translation strategies are mentioned, most notably Davies and Epstein. The results of this thesis indicate that Lempinen has favoured certain translation strategies for certain types of names, although the results should not be generalised. Each of the human character names has been translated with the same translation strategy, but other categories of names contain more variation regarding what translation strategies have been used. Therefore, most of Lempinen’s translation choices cannot be generalised and they seem to be dependent on the type of name and its connotations.
Keywords: fantasy literature; nomenclature; proper nouns; translation; translation strategies.